До питання інституалізації мусульманської спільноти України: духовне управління мусульман України "Умма" - Брильов, Д. (Київський національний університет імені Тараса Шевченка, 2018)
Стаття присвячена питанню інституалізації мусульманської спільноти України на прикладі Духовного управління мусульман України. Показано, що поява управління певною мірою являло собою легітимацію релігійної діяльності ВАГО "Альраід" через афілійований з нею муфтіят. Головними напрямками діяльності муфтіяту є межрелігійний діалог, соціальна та просвітницька діяльність. Важливою складовою функціонування ДУМУ "Умма" є формування україномовного ісламського дискурсу, який подекуди має націоналістичне забарвлення.

The article is devoted to the issue of institutionalization of the Muslim community of Ukraine on the example of the Spiritual Administration of the Muslims of Ukraine, known as 'Umma' (Dukhovne upravlinnia musul′man Ukraïny 'Umma' – DUMU-Umma) which was founded in 2008. This article is based on an analysis of audio and video materials available on the Internet, press articles and the religious literature and periodicals published by DUMU-Umma, as well as interviews with mufti of DUMU-Umma Said Ismagilov. The purpose of the paper is to study the features of the emergence and development of this spiritual administration, as well as the distinctive characteristics of the DUMU-Umma. It is shown that the appearance of this spiritual administration to a certain extent was a legitimation of the religious activities of the All-Ukrainian Association "Alraid" through the Muftiyat affiliated with it. The main areas of activity of the DUMU-Umma are interreligious dialogue, first of all with representatives of the Ukrainian Greek Catholic Church (UGCC) and the Ukrainian Orthodox Church of the Kyiv Patriarchate (UOC-KP), as well as social and educational activities. Important part of the social activity of DUMU-Umma is charitable activity, participation in volunteer projects, assistance to migrants and military personnel located in the ATO zone. It is shown that the DUMU-Umma is closely connected with the organizations that are part of the transnational network "Muslim Brotherhood", and their ideological affinity is also noted. An important part of the functioning of DUMU-Umma is the formation of Ukrainian-language Islamic discourse with nationalistic markers. At the same time, the choice of national-oriented rhetoric is largely due to the attempt to find its niche in the Muslim community of Ukraine, as well as to the confrontation between DUMU-Umma and its main competitor in the Muslim community of Ukraine, the Spiritual Administration of the Muslims of Ukraine (DUMU) headed by Sheikh Ahmed Tamim.
Institutionalization of the muslim community of Ukraine: the spiritual administration of muslims of Ukraine "UMMA"
Keywords: іслам в Україні; ДУМУ "Умма"; Брати-мусульмани; Islam in Ukraine; DUMU-Umma; Muslim Brotherhood.